Is the use of high frequency oscillatory ventilator beneficial in managing severe chest injury with massive air leak?. (5th November 2014) - Dev Soni, Kapil; Aggarwal, Richa; Gupta, Amit; Sharma, Pawan
Abstract : Severe thoracic trauma can be associated with immediate life-threatening injuries including major air leak syndrome that can lead to acute respiratory failure and refractory hypoxaemia. Such injuries invariably require thoracotomy following failure of conventional ventilation strategy and paucity of other non-operative interventions. We describe a case in which we used high frequency oscillatory ventilation (HFOV) as a part of management of such injury and averted the need for thoracotomy.